High fluoride drinking water in Gokwe, northwest Zimbabwe - Mamuse, Antony; Watkins, Ron (IWA Publishing, 2016)
More than 200 million people worldwide are exposed to excessive fluoride in drinking water. According to the World Health Organization, the optimal concentration range of fluoride in drinking water is 0.5 to 1.5 mg/L. Above this range, populations may contract dental fluorosis or, in severe cases, crippling skeletal fluorosis. In the Gokwe area in NW Zimbabwe, where drinking water contains up to 11 mg/L fluoride, fluorosis prevalence has previously been estimated at 62%. This paper investigates the water quality of 126 water sources in Gokwe (58 pumped boreholes, 15 flowing artesian boreholes, 46 wells and 7 streams). The water chemistry, determined from high performance ion chromatography and field measurements, showed that the water source types exhibit significantly different (P < 0.05) concentrations of F , Cl , Naþ, Kþ, Ca2þ, Mg2þ, temperatures, pH and conductivity values. Thirty-five (28%) of the 126 water sources (18 pumped boreholes, 15 artesian boreholes, one well and one stream) contained F > 1.5 mg/L, indicating that fluoride contamination in the area is a characteristic of deeper groundwater, possibly due to its interactions with the potentially fluoridic coaly and carbonaceous materials of the Lower Karoo Aquifer at depth. The plausibility of providing alternative low fluoride water, and defluoridation, should be investigated.